2019
DOI: 10.1101/757419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PTPN2 deletion in T cells promotes anti-tumour immunity and CAR T cell efficacy in solid tumours

Abstract: Although adoptive T‐cell therapy has shown remarkable clinical efficacy in haematological malignancies, its success in combating solid tumours has been limited. Here, we report that PTPN2 deletion in T cells enhances cancer immunosurveillance and the efficacy of adoptively transferred tumour‐specific T cells. T‐cell‐specific PTPN2 deficiency prevented tumours forming in aged mice heterozygous for the tumour suppressor p53. Adoptive transfer of PTPN2‐deficient CD8+ T cells markedly repressed tumour formation in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 82 publications
2
48
0
Order By: Relevance
“…These phenotypes have been attributed to the important role of PTPN2 in regulating activation of Janus kinases ( 40 ); signal transducers and regulators of transcription-1 (STAT1), STAT3, and STAT5 ( 41 ); as well as T cell receptor (TCR) signaling ( 38 ). Consistent with the key role of PTPN2 loss of function in autoimmunity, recent studies have also validated PTPN2 as an important target for cancer immunotherapy ( 42 , 43 ).…”
Section: Introductionmentioning
confidence: 56%
“…These phenotypes have been attributed to the important role of PTPN2 in regulating activation of Janus kinases ( 40 ); signal transducers and regulators of transcription-1 (STAT1), STAT3, and STAT5 ( 41 ); as well as T cell receptor (TCR) signaling ( 38 ). Consistent with the key role of PTPN2 loss of function in autoimmunity, recent studies have also validated PTPN2 as an important target for cancer immunotherapy ( 42 , 43 ).…”
Section: Introductionmentioning
confidence: 56%
“…(21)(22)(23)(24). Recent researches demonstrated that PTPN2 deletion can enhance the effectiveness of anti-tumor immunity (8,25,26). Thus, PTPN2 expression is likely to possess potential medical significance in STAD and could be exploited as an attractive immunotherapy target.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of PTPN6 with the loss of pSTAT3 expression could be chosen as a biomarker for the prognosis of peripheral-T cell lymphoma (7). One research published recently noted that a deficiency of PTPN2 could enhance antitumor immunity and the therapeutic efficacy of CAR T cells to solid cancers (8). PTPN22 plays an important part in regulating autophagy and NLR family pyrin domain containing 3 inflammasome activation (9).…”
Section: Introductionmentioning
confidence: 99%
“…Protein tyrosine phosphatase non-receptor type 2 (PTPN2) has recently been suggested as a possible target for tumor therapy (11)(12)(13). PTPN2 is a ubiquitously expressed anti-inflammatory protein known to regulate pro-inflammatory signaling pathways by direct dephosphorylation, including several Janus kinases, signal transducer and activator of transcription (STAT) family members and others (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that loss of PTPN2 in myeloid cells and intestinal epithelial cells reduce tumor load and promote immune responses against tumors in a model of colitis-associated colon cancer by increasing IL-1 production and elevating immunogenicity of the tumor (19). Tumor cell-specific and T-cell-specific PTPN2 deletion has been reported to reduce tumor load in subcutaneous tumor models using melanoma and CRC cell lines as well as in mammary tumor models (11)(12)(13). In humans, reduced PTPN2 expression correlated with better treatment response in Tcell acute lymphoblastic leukemia in children (20).…”
Section: Introductionmentioning
confidence: 99%